2005
DOI: 10.1089/pho.2005.23.451
|View full text |Cite
|
Sign up to set email alerts
|

Pure or Tarnished: Are Systematic Reviews Blind or Biased?

Abstract: EditorialPure or Tarnished: Are Systematic Reviews Blind or Biased?I T SEEMS that the current mindset of the government, payors, and various watchdog groups is to hold the medical and scientific communities to practices and treatments that are "evidence based." This concept is certainly laudable and is definitely not new. We live in an age of rapidly changing technologies, with vast amounts of information being offered via the scientific literature, the lay press, infomercials, the Internet, and various other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Even though others have offered detailed comments, analysis and meta-analysis of the literature [74][75][76][77][78][79][80][81][82], the strong positive findings of our study warrant further discussion of the clinical value of phototherapy, given the widespread perception that the literature is replete with contradictory data. For example, treatment of nine patients with 12 ''minor postsurgical wounds'' using 300 mW cm À2 irradiance and 9 J cm À2 fluence of 830 nm light was reported to be ineffective in promoting wound closure or reducing the pain caused by the incisions [83].…”
Section: Discussionmentioning
confidence: 69%
“…Even though others have offered detailed comments, analysis and meta-analysis of the literature [74][75][76][77][78][79][80][81][82], the strong positive findings of our study warrant further discussion of the clinical value of phototherapy, given the widespread perception that the literature is replete with contradictory data. For example, treatment of nine patients with 12 ''minor postsurgical wounds'' using 300 mW cm À2 irradiance and 9 J cm À2 fluence of 830 nm light was reported to be ineffective in promoting wound closure or reducing the pain caused by the incisions [83].…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, a brief comment seems warranted considering this aspect of our results, even though others have offered detailed comments and analysis of the literature in the past. [54][55][56][57] Lagan et al 58 used 830-nm light to treat nine patients with 12 "minor postsurgical wounds" using 300 mW cm Ϫ2 irradiance and 9 J/cm Ϫ2 fluence; they found no difference in wound closure and no difference in pain levels between patients in the treatment group and controls. Our finding that small-sized ulcers or minor wounds tend to heal properly regardless of phototherapy support their results.…”
Section: Discussionmentioning
confidence: 99%
“…The issues regarding conflicts and bias in randomized trials and the evidence based literature have been frequent topics considered in this column. [2][3][4][5][6][7][8] We have examined bias in study development, conduct, and reporting, and have echoed the concerns of Bjordal and others who have demonstrated that systematic reviews themselves are biased in their analysis of the "evidence base" and the subsequent recommendations promulgated as a result thereof. 5 The topics continue to receive notoriety as authors have considered "gizmo idolatry," 9 the influence of "industry influence," 10 the "quality" of RCTs of efficacy research in complementary and alternative medicine, 11 and the assessment of physician and patient preferences on research.…”
mentioning
confidence: 97%